Socio-demographic Factors affecting reading comprehension achievement among secondary school Students with learning disabilities in Ibadan, Nigeria (2020)
The study examined the influence that socio-demographic factors (school social environment, type of school and gender) have on achievement in reading comprehension of students with learning disabilities. The study employed the correlational design. One hundred and twenty- three (123) Junior Secondary Class 1 (JSS 1) students with learning disabilities from six secondary schools (3 private and 3 public) ail located in Ibadan North Local Government Area, Ibadan, Oyo State, Nigeria participated in the study. Three scales namely: the Pupil Rating Scale (Revised), the Comprehensive School Climate Inventory (adapted) and the Test of Reading Comprehension were administered to the participants and the scores derived from these were subjected to Pearson Product Moment Correlation, Multiple Regression and t-test Statistics. The results revealed that the most potent factor in the prediction of reading comprehension achievement of students with learning disabilities is school social environment (r =0.214) followed by gender (r =0.185). The joint contribution of school social environment, school type and gender on reading comprehension achievement of students with learning disabilities was significant. While school social environment could considerably and independently predict reading comprehension achievement among students with learning disabilities, school type and gender could not. Further findings showed a significant difference in reading comprehension achievement between male and female students with learning disabilities (Cal.t = 2.075). Also, there was no observable significant difference in the reading comprehension achievement of students with learning disabilities in private and public schools. Therefore, it was suggested that teachers of students with learning disabilities should ensure that reading comprehension lessons take place in stimulating and conducive classroom environments devoid of unhealthy, risky and distracting stimuli.